The tradition of urban storytellin - Domokos, Mariann (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2024)
The most trivial way of transmitting culture is through oral storytelling, which cannot be exclusively linked to specific periods or social strata. The paper starts from the premise that storytelling in modern urban environment and the stories told in these settings (literary tales, folk- and fairy tales etc.) are also part of the Hungarian narrative tradition. The production and consumption of fictional narratives are not only a prominent social event in traditional folk culture, but also in modern popular culture. With these considerations in mind the present essay has examined the actors, institutions, occasions and customs of artistic, urban storytelling in Hungary at the end of the long 19th century (from the 1890s to the Second World War) based on contemporary Hungarian printed press publications and archival sources. The new urban forums for public storytelling were brought into being by the modern bourgeois which was inextricably linked to the development of children’s literature and the artistic demands of children’s entertainment were organized by the capital’s intelligentsia, artists, writers, poets and actors in Budapest. At the turn of the 19th century, an international trend towards artistic storytelling based on library institutions has emerged and subordinated to public education in Anglo-Saxon countries. These library efforts were also adopted by Hungarian professionals, but a different kind of Hungarian storytelling movement, based on theatrical, artistic children’s entertainment, dates back much earlier and was much more significant. Children’s magazines such as Az Én Ujságom [My Newspaper], edited by Lajos Pósa, were an important step in the institutionalisation of Hungarian children's literary culture. Pósa has organized storytelling events from the early 1890s that have served the interests of the publishing house of the newspaper as well as the promotion of children's literature and authors alike. These events in the following decades provided an inspiring model for a wide range of independent cultural children’s storytelling occasions in which marketing and charitable functions are effectively combined. The paper examines the storytelling events organized by literary children’s magazines, by the Magyar Telefonhírmondó [Hungarian Telephone Herald, a long life telephone newspaper system] and a special outdoor children’s storytelling-series in the Budapest Zoo. In addition, the paper draws attention to the fact that the Hungarian acting education system included the teaching of stage storytelling from 1900, in which Jenő Balassa, the professional storyteller known as Basa bácsi [Uncle Basa] played a huge role.
Keywords: children’s litearure; mass entertainment; mediality; staged storytelling; story hours in the library; artistic education